Effect of a Sodium and Calcium DL-β-Hydroxybutyrate Salt in Healthy Adults - Fischer, Tobias; Och, Ulrike; Klawon, Ira; Och, Tim; Grüneberg, Marianne; Fobker, Manfred; Bordewick-Dell, Ursula; Marquardt, Thorsten (Journal of Nutrition and Metabolism, 2018)
Background. Ketone body therapy and supplementation are of high interest for several medical and nutritional fields. The intake of ketone bodies is often discussed in relation to rare metabolic diseases, such as multiple acyl-CoA dehydrogenase deficiency (MADD), that have no alternatives for treatment. Case reports showed positive results of therapy using ketone bodies. The number of ketone body salts offered on the wellness market is increasing steadily. More information on the kinetics of intake, safety, and tolerance of these products is needed. Methods. In a one-dose kinetic study, six healthy subjects received an intervention (0.5 g/kg bw) using a commercially available ketone body supplement. The supplement contained a mixture of sodium and calcium D-/L-β-hydroxybutyrate (βHB) as well as food additives. The blood samples drawn in the study were tested for concentrations of D-βHB, glucose, and electrolytes, and blood gas analyses were done. Data on sensory evaluation and observed side effects of the supplement were collected. The product also went through chemical food analysis. Results. The supplement led to a significant increase of D-βHB concentration in blood 2.5 and 3 h after oral intake (p=0.033; p=0.043). The first significant effect was measured after 2 h with a mean value of 0.598 ± 0.300 mmol/L at the peak, which was recorded at 2.5 h. Changes in serum electrolytes and BGA were largely unremarkable. Taking the supplement was not without side effects. One subject dropped out due to gastrointestinal symptoms and two others reported similar but milder problems. Conclusions. Intake of a combination of calcium and sodium D-/L-βHB salt shows a slow resorption with a moderate increase of D-βHB in serum levels. An influence of βHB salts on acid-base balance could not be excluded by this one-dose study. Excessive regular consumption without medical observation is not free of adverse effects. The tested product can therefore not be recommended unconditionally.